Peningkatan Hasil Pembelajaran HOTs Mata Pelajaran Bahasa Inggris Materi Expressing Giving Compliment and Congratulation Melalui Scientific Approach Model Pembelajaran Abad Ke-21 Metode Blended Learning Peserta Didik Kelas X.IPK.3 MAN 2 Kota Payakumbuh - Josmartin Peto (Departement of Mathematics Education, 2022)
This study aims to see and analyze the increasing in learning outcomes of students in class X.IPK.3 Payakumbuh Odd Semester for the 2021/2022 Academic Year, in English subjects Expressing Giving Compliment and Congratulation Materials through the Scientific Approach of the 21st Century Learning Model Blended Learning Method in HOTS learning. This research was conducted using the Classroom Action Research method which consisted of two cycles, where each cycle consisted of: planning, action, reflection, and evaluation. It was conducted from August to November 2021. The data was processed in each cycle and then analyzed using percentages. The results obtained in the pre-cycle, cycle I and cycle II showed an increase. The average grade for students' knowledge increased from 49.31 with 0% completeness in the pre-cycle to 73.43 to (41.67%) in the first cycle and 77.70 (77.78%) in the second cycle. Here it can be seen that the percentage of students who did not complete decreased. The average value of the skill class was significant. It is proven by the gain from 80.56 in the pre-cycle to 84.51 (4.90%) in the first cycle, and to 93.61 (10.77%) in the second cycle. In each action, all students complete 100%. Based on the results of the second cycle assessment, it can be interpreted that the implementation of the 21st Century Scientific Approach Learning Model Blended Learning Method can improve students' high-level English learning outcomes, although the increase is not in line with expectations, but it is quite effective in learning English. The conclusion obtained from this research is that the use of the Scientific Approach 21st Century learning model with the Blended Learning method in HOTS learning can improve student learning outcomes.